139-3x=42x+19

Simple and best practice solution for 139-3x=42x+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 139-3x=42x+19 equation:


Simplifying
139 + -3x = 42x + 19

Reorder the terms:
139 + -3x = 19 + 42x

Solving
139 + -3x = 19 + 42x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42x' to each side of the equation.
139 + -3x + -42x = 19 + 42x + -42x

Combine like terms: -3x + -42x = -45x
139 + -45x = 19 + 42x + -42x

Combine like terms: 42x + -42x = 0
139 + -45x = 19 + 0
139 + -45x = 19

Add '-139' to each side of the equation.
139 + -139 + -45x = 19 + -139

Combine like terms: 139 + -139 = 0
0 + -45x = 19 + -139
-45x = 19 + -139

Combine like terms: 19 + -139 = -120
-45x = -120

Divide each side by '-45'.
x = 2.666666667

Simplifying
x = 2.666666667

See similar equations:

| (x^1/2)(3x-3)=0 | | 4x/5x=23/3 | | (x^(1/2))(3x-3)=0 | | x^(1/2)((3x-3))=0 | | Y=-1/3x-3 | | Y=-1/3x-3 | | 99+4x=10x+15 | | x^(1/2)(3y-3)=0 | | -1/3x-3 | | 4x/5x=72/3 | | x=aP+b | | 2x/3-8=1x-7 | | (2/3x)=(4x-2/6) | | -8-y=12-0y | | 4x+3(x-2)=7(x-2)+8 | | 9(-8)-13=-31 | | mxn=2-d | | m*n=2-d | | 4(x+2)+6=2x+2x+14 | | 5a^3(5a^2+2)= | | 3x+7-x=2x+21 | | 3x(4x+3-5)=58 | | 10/x=3/2x+34 | | 6s-3(5s+2)=4-5s | | y=0.5x^2-3x+4 | | 5a^3(5a^2+2)=25a^5+10a^3 | | (6-x)(6+x)-(x-11)x=18 | | x+(-1/2)=4 | | x=4.2+-0.5y | | 10x+5y=42 | | 5y=3x+2forx | | 4.00/5.00x=20 |

Equations solver categories